An empirical method for deriving RBE values associated with electrons, photons and radionuclides. Issue 4 (30th January 2015) - Bellamy, M.; Puskin, J.; Hertel, N.; Eckerman, K.
Abstract: There is substantial evidence to justify using relative biological effectiveness (RBE) values of >1 for low-energy electrons and photons. But, in the field of radiation protection, radiation associated with low linear energy transfer has been assigned a radiation weighting factor w R of 1. This value may be suitable for radiation protection but, for risk considerations, it is important to evaluate the potential elevated biological effectiveness of radiation to improve the quality of risk estimates. RBE values between 2 and 3 for tritium are implied by several experimental measurements. Additionally, elevated RBE values have been found for other similar low-energy radiation sources. In this work, RBE values are derived for electrons based upon the fractional deposition of absorbed dose of energies less than a few kiloelectron volts. Using this empirical method, RBE values were also derived for monoenergetic photons and 1070 radionuclides from ICRP Publication 107 for which photons and electrons are the primary emissions.